Enough already eaudiobook Learning to love the way i am today. - Bertinelli, Valerie (HarperAudio, 2022)
A #1 NEW YORK TIMES BESTSELLER Beloved actress, Food Network personality, and New York Times bestselling author Valerie Bertinelli reflects on life at sixty and beyond. Behind the curtain of her happy on-screen persona, Valerie Bertinelli's life has been no easy ride, especially when it comes to her own self-image and self-worth. She waged a war against herself for years, learning to equate her value to her appearance as a child star on One Day at a Time and punishing herself in order to fit into the unachievable Hollywood mold. She struggled to make her marriage to Eddie Van Halen — the true love of her life — work, despite all the rifts the rock-star lifestyle created between them. She then watched her son follow in his father's footsteps, right up onto the stage of Van Halen concerts, and begin his own music career. And like so many women, she cared for her parents as their health declined and saw the roles of parent and child reverse. Through mourning the loss of her parents, discovering more about her family's past, and realizing how short life really is when she and her son lost Eddie, Valerie finally said, "Enough already!" to a lifelong battle with the scale and found a new path forward to joy and connection. Despite hardships and the pressures of the media industry to be something she's not, Valerie is, at last, accepting herself: she knows who she is, has discovered her self-worth, and has learned how to prioritize her health and happiness over her weight. With an intimate look into her insecurities, heartbreaks, losses, triumphs, and revelations, Enough Already is the story of Valerie's sometimes humorous, sometimes raw, but always honest journey to love herself and find joy in the everyday, in family, and in the food and memories we share. "This thoughtful, bighearted book is sure to be a hit with Bertinelli fans and those with an appetite for stories of hard-won self-acceptance. A warmly intimate memoir." – Kirkus Reviews "In a series of brutally frank essays, Bertinelli looks back on the emotional struggles and triumphs of her life. By turns raw and inspiring, this contains a little bit of wisdom for everyone." – Publishers Weekly